Development and initial validation of the Partnership Scale-DanceSport Couples - Liu, Xiuxia; Yang, Guan; Wang, Shen; Wang, Xiangfei; Wang, Xuelian (Frontiers in Psychology, 2023)
Introduction: Dancesport is considered as a male-female partner dancing. Its important to understand partnership between dance couples so that their competitive performance can be effectively supported. However, there is a dearth of empirical research on the effects of partnerships on competitive performance due to a lack of appropriate assessment tools. Aims: This multi-study paper outlines the development, content and construct validity of a novel, mixed-method tool to assess Chinese dance sport partnership. Methods: The development of the PS-CDSC included four studies and data from four samples of athletes (N=914 total). In stage one, outlined in study one, PS-CDSC items were generated and then refined using feedback provided by academics, sport coaches, and athletes. In stage two, outlined in studies two and three, exploratory factor analysis, confirmatory factor analysis were used to examine the structure of PS-CDSC items. In stage three, outlined in study four, composite reliability, discriminant validity and convergent validity were assessed. The result of this process was a 13-item three-factor instrument. Based on these initial findings, the PS-CDSC provides the first valid and reliable way of measuring partnership between Chinese dancesport couples. Conclusion: This study has taken a promising first step in developing a tool to comprehensively measure partnership between Chinese dancesport couples.